Two great Marias of the nation (Confluenţe Bibliologice, 2025)
The author of article is share with experience of organizing the exhibition „Two Great Marias of the Nation”. The exhibition comprises more than 90 books, periodicals, CDs, DVDs, vinyl records, documents about the life and work of the famous opera singers Maria Bieşu and Maria Cebotari. The notorious women contributed to the cultural and spiritual development of our country.
Keywords: Bieșu Maria (1935 – 2012); Cebotari Maria (1910- 1949); thematic exhibition